Environmental Performance and Firm Value: Profitability as a Moderator - Alfiyah Aditya Rahmawati; Anis Chariri (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
The objective of this study was to ascertain how the firm's value is influenced by environmental performance, using profitability as a moderating factor. Additionally, it sought to compare firm value, profitability, and ecological before, during and after Covid-19. The study used secondary data for a sample size of 50 manufacturing companies and participants in PROPER from 2019 to 2022. The results show no discernible relationship between firm value and environmental performance. The correlation between firm value and environmental performance is strengthened by the noteworthy positive moderation effect of probability. The firm value continued to drop both during and after the Covid-19 era. Environmental performance and profitability during COVID-19 show a decrease, but after 2022, both tend to be able to increase again, similar to the pre-COVID-19 period. The originality of this research lies in examining the comparisons before, during and after COVID-19 on environmental performance, firm value and profitability. Future research ideas include utilizing additional independent variables (e.g., CSR, company size, board of commissioners) that can impact firm value, as well as using alternative environmental performance measurements other than PROPER